Influence of deformation degree at cold-rolling on the anneal hardening effect in sintered copper-based alloys - Nestorović Svetlana (Journal of Mining and Metallurgy. Section B: Metallurgy)
Samples of copper-based alloys, Cu-4at%Zn, Cu-8at%Zn and Cu-5at%Ni-2at%Sn and pure copper have been prepared by a powder metallurgical method. The samples were subjected to cold rolling to 30, 50 and 70% in reduction, followed by annealing up to the recrystallization temperatures. Anneal hardening effect has been observed with the alloys in an annealing temperature range of 180-4000C, the hardness being increased with the amount of reduction at the prior cold - rolling.